Trends in Beef Calf Lots by Single Breed Sire Groups Marketed via Video Auction from 2010 Through July 14, 2017 - E. D. McCabe; M. E. King; K. E. Fike; K. L. Hill; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The objective was to characterize the potential change in the percentage of lots of beef calves sired by a single breed marketed via video auction from 2010 through July 14, 2017. Study Description:Information describing factors about lots sold through a livestock video auction service (Superior Livestock Auction, Fort Worth, TX) was obtained in electronic format. Sire breed of a lot was determined based on the description provided by sellers. All calves in a lot were sired by a single breed and a minimum of 50 lots were required for the analysis. The Cochran-Armitage trend test was used to determine an increasing or decreasing trend over time with a P≤0.05 considered significant. The Bottom Line:Producers marketing calves via video auction may be changing the genetics of their sires to use on a primarily black cow herd.
Keywords: beef calves; sire breed; video auctions